Social Intermediaries: Creating A More Responsible Web Through Portable Identity, Cross-Web Reputation, And Code-Backed Norms - Kahn, Daniel H. (Science and Technology Law Review, 2009)
Currently, our identities are scattered across the Web. At each website on which we participate, we must create new user names, personal profiles, social connections, and histories of activity. Without portable identities, we cannot fully reap the benefits of the emerging reputation economy. Moreover, because of the Web’s structural limitations on identity, norm-based social governance has not played a significant role on most sites. The paucity of norms has created an atmosphere in which abusive behavior is common, heightening the apparent need for new legal regulation. However, new tools, which I term social intermediaries, are poised to introduce portable identity to the Web. By allowing users to aggregate records of their activities across multiple sites, these tools increase reputation-based incentives for production. They also promote an atmosphere of respect by encouraging people to recognize each other as fully rounded individuals. Most importantly, they will allow many more sites to offer opportunities for users to govern each other through code-backed norms. This new opportunity for bottom-up social governance will help responsible users and site operators ameliorate the problems of abusive behavior on the Web. While social intermediaries introduce new regulatory challenges, their norm-building capacity shows that law is not the only answer to the Web’s social problems.